Implementation of Tajweed Learning with Jigsaw Strategy and Contextual Learning - Kasman, Kasman; Rahman, Aulia (Letiges, 2023)
The purpose of this research is motivated by religious learning that uses more lectures or da'wah methods. In contrast, Islamic religious education, specifically in tajwid, should use more practice and contextual, including educators' need for more attention in providing motivation and innovation in the learning process. This study uses a qualitative method with a social, educational approach. This type of research is field research, so the data obtained comes from the practice of tajwid teacher learning using observation and interviews. The study results on implementing the Jigsaw and Contextual Learning strategies in Islamic learning, especially in tajwid learning at the Mandailing Natal State Islamic College, use the seven essential components of the Jigsaw strategy. Then later in its implementation, students study in groups with cooperative techniques and try to be responsible for the assignments given. Using the seven essential components of the Jigsaw strategy is an original contribution to learning the Islamic religion. In addition, the implementation of group learning using cooperative techniques and emphasizing student responsibility for the assignments given also provides added value in this research.